Clinical Practice Pattern of Korean Medicine Doctors in Idiopathic Short Stature Treatment: A Survey Study. (10th August 2022) - Jang, Soobin; Lee, Boram
Abstract : Background . Korean medicine (KM) interventions are attractive for children with idiopathic short stature (ISS). We investigated the real-world clinical practice patterns of KM doctors in ISS treatment. Methods . The survey targeted KM doctors who have treated patients with ISS in KM clinical settings for >3 years. We included questions on the diagnosis and treatment patterns, effects, cost, and opinions of doctors on KM treatment for ISS. A frequency analysis was performed. Results . There were 58 respondents, and "heights of parents" ( n = 57, 98.3%), "height, weight, and growth rate of child" ( n = 55, 94.8%), and "amount of meals, digestive function" ( n = 52, 89.7%) were frequently used as indicators for diagnosis and treatment. The most frequently used KM interventions were "herbal medicine" ( n = 58, 100%), "acupuncture" ( n = 49, 84.5%), "moxibustion" ( n = 38, 65.5%), "dry cupping" ( n = 26, 44.8%), and "physiotherapy" ( n = 22, 37.9%). Herbal medicines were generally prescribed to tonify the spleen or kidney, and the most frequently used individual herbs were Acanthopanacis cortex, Astragali Radix, and Cervi parvum cornu . The most common acupuncture points were ST36, GB34, SP6, EX-LE5, and LI4. Conclusions . This study showed the use of KM for ISS in real-world clinical settings. In the future, well-designed clinical studies to verify the effect of KM treatment on ISS based on real-world clinical practice patterns should be actively performed.